Characteristics of the Resource Basis of the Research of the History of the Development of the Staff Potential of High Educational Establishments in Ukraine - Maryna Razorenova (Pedagogical Discourse, 2013)
The structure and compounds of the resource basis of the research of the history of the development of the staff potential of high educational establishments in Ukraine in the second part of the 20th century have been grounded in the article. It consists of three groups of sources: the work the analysis of which enables us to develop a methodology of the research;  the works the main points of which are the theoretical basis of the study; variety of documents, in which the specific cases of human resource development in the Ukrainian universities during defined period  and earlier  have been reflected. The use of these sources in complex has been proved to enable tracing the peculiarities, identifying the tendencies and regularities, grounding the principles and working out the management programs and models of the development of the staff potential of the universities. The implementation of the enumerated above is the guarantee of the successful accession of Ukrainian universities to the world educational space.